Obstructive azoospermia secondary to bilateral epididymal cystadenomas in a patient with von Hippel-Lindau - Patrick T. Gomella; Paul Shin; Ramaprasad Srinivasan; W. Marston Linehan; Mark W. Ball (Urology Case Reports, 2019)
von Hippel-Lindau (VHL) is a heritable cancer syndrome associated with findings in multiple organ systems. Male patients can be affected by epididymal cystadenomas which are benign tumors localized to the epididymis. While benign, these tumors can cause pain and in very rare circumstances can have an effect on fertility especially when present bilaterally. We present a case of a young man with obstructive azoospermia secondary to bilateral cystadenomas, with a focus on his work-up and management. Keywords: VHL, von-Hippel Lindau, Epididymal obstruction, Obstructive azoospermia, Sperm retrieval